Differences between Early and Late-Onset Alzheimer’s Disease in Neuropsychological Tests - Sá, Francisca; Pinto, Paula; Cunha, Catarina; Lemos, Raquel; Letra, Liliana; Simões, Mário; Santana, Isabel (Frontiers in Neurology, 2012)
Although patients with Alzheimer disease (AD) share clinical and histological features regardless of age of onset, the hypothesis that early-onset AD constitutes a distinct subgroup prevails. Some authors suggest that early attention or language impairment constitute patterns of differentiation in terms of neuropsychological profile. However, investigations are not consensual in terms of cognitive domains affected in each group. Aim: To investigate whether there is early neuropsychological difference between two types of AD using the conventional dividing line of 65 years. Methods: We evaluated the results obtained in the Mini-Mental State Examination (MMSE) and in a comprehensive neuropsychological battery – Battery of Lisbon for the Assessment of Dementia (BLAD), at a Dementia clinic in the University Hospital of Coimbra and a Memory Clinic. Consecutive patients with a clinical probable diagnosis of mild to moderate AD, using standard criteria (DSMIV and NINCDS-ADRDA), were selected. Statistical analysis was performed using Qui-square and U-Mann-Whitney, for categorical and non-categorical variables. Results: The sample included 280 patients: 109 with early-onset AD and 171 with a late-onset form. Groups were comparable in gender, education, severity of disease and MMSE. In BLAD, the early onset group had lower scores in Naming (p=0,025), Right-Left Orientation (p=0,029) and Praxis (p=0,001), and better performances in Orientation (p=0,001) and Visual Memory (p=0,022). After application of Bonferroni correction for multiple comparisons only Praxis and Orientation could differentiate the two groups. Discussion: The results are suggestive of dissociated profiles between early and late-onset AD. Younger patients have a major impairment in Praxis and a tendency for a great impairment in neocortical temporal functions. Late-onset form had a tendency for worse performances in Visual Memory and Orientation, suggesting a more localized disease to the limbic structures